Selenium nanoparticle-delivered MDM2 inhibitor reactivates p53 and reprograms tumor immune microenvironment in colorectal cancer - You, Weiming; Feng, Jun; Guo, Litao; Yan, Jin; Yan, Siqi (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) remains a major global health challenge, with limited immunotherapy efficacy in microsatellite stable (MSS) tumors that comprise ~85% of cases. The p53 tumor suppressor pathway, frequently inactivated through the mouse double minute 2 homolog (MDM2) overexpression in wild-type tumor protein 53(TP53) tumors, represents a promising therapeutic target for both direct antitumor effects and immune modulation.MethodsWe developed selenium nanoparticles loaded with the MDM2-targeting peptide inhibitor MI (Se@MI) using a one-pot synthesis approach. The nanoparticles were characterized by transmission electron microscopy, dynamic light scattering, and UV-Vis spectroscopy. In vitro assays included MTT cytotoxicity evaluation, cellular uptake by flow cytometry, RNA-seq, and Western blotting of p53-pathway/apoptosis markers. Antitumor efficacy was evaluated in CT26 murine colorectal cancer models, with mechanistic studies including transcriptomic analysis, immunohistochemistry, and flow cytometry. Safety profiles were assessed through body weight monitoring, hematological analysis, histopathological examination of major organs, and serum biomarker evaluation.ResultsSe@MI nanoparticles demonstrated uniform spherical morphology (45-50nm diameter) and displayed a positive zeta potential (+24.69 mV), indicative of favorable colloidal dispersibility. Enhanced cellular uptake (74.3% positive cells) and potent cytotoxicity (IC50 = 1.00 μM) were observed in CT26 cells. Transcriptomic analysis revealed significant activation of p53 signaling pathways (NES = 1.504, P = 0.029) and protein analyses confirmed induction of p21, PUMA, Bax, and cleaved caspase-3. In vivo, Se@MI treatment achieved 72.23% tumor growth inhibition, significantly outperforming controls. Mechanistically, Se@MI restored p53 function by disrupting MDM2-p53 interactions, inducing apoptosis and cell cycle arrest. Importantly, Se@MI reprogrammed the tumor immune milieu through increased infiltration of CD8+ T cell and cytotoxic function while suppressing regulatory T cells. Comprehensive safety evaluation revealed excellent biocompatibility with no adverse effects on body weight, hematological parameters, organ histology, inflammatory cytokines, or hepatic/renal function markers.ConclusionsSe@MI represents a novel nanomedicine strategy that combines direct p53 pathway reactivation with immune microenvironment modulation. This dual mechanism of action offers a potential strategy to boost immunotherapeutic outcomes in colorectal carcinoma and may help overcome resistance mechanisms to immune checkpoint blockade.